1995
DOI: 10.1155/1995/85036
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Early Fetal‐Liver Hemopoietic Stem Cellsof the Rat Using Monoclonal Antibodies Against theTransferrin Receptor, Thy‐1, and MRC‐Oχ82

Abstract: Rat bone-marrow colony-forming units in the spleen (CFUs-12) were found to lack the surface antigens recognized by the monoclonal antibodies CD53 (MRC-OX44), MRC-OX39, MRC-OX59, and 144.2.15. These would provide a strategy for their enrichment by depletion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…These cells largely expressed CD45, CD43, and CD53 antigens. A similar phenotype has recently been described in cell progenitors from early fetal rat liver (Crook and Hunt, 1996), suggesting that cells reaching the rat thymic rudiment could already express these cell markers. The expression of high-Mr isoform of the leukocyte common antigen (CD45) has been demonstrated in adult human (Deans et al, 1991), mouse (Goff et.al., 1990), and rat (Law et expression on them of MHC class I and class II molecules, and the acquisition of first specific cortical-and medullary epithelial-cell markers (Vicente et al, 1996).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These cells largely expressed CD45, CD43, and CD53 antigens. A similar phenotype has recently been described in cell progenitors from early fetal rat liver (Crook and Hunt, 1996), suggesting that cells reaching the rat thymic rudiment could already express these cell markers. The expression of high-Mr isoform of the leukocyte common antigen (CD45) has been demonstrated in adult human (Deans et al, 1991), mouse (Goff et.al., 1990), and rat (Law et expression on them of MHC class I and class II molecules, and the acquisition of first specific cortical-and medullary epithelial-cell markers (Vicente et al, 1996).…”
Section: Discussionsupporting
confidence: 78%
“…The rat thymic primordium is colonized around fetal day 14 by cell progenitors, the phenotype of which has not been clearly established although the expression on them of different cell markers has been reported 4981. E-mail: Zapata@eucmax.sim.ucm.es (Ritter et al, 1978;Paterson and Williams, 1987;Kampinga and Aspinall, 1990;Crook and Hunt, 1996). Moreover, the existence, as reported in mice (Godfrey et al, 1993), of cell subpopulations defined by the expression of CD44 and CD25 in the DN-cell compartment of rats is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…It is confirmed, however, that rat CD90(Thy‐1) antigen is present on pluripotent stem cells in bone marrow, neonatal spleen and fetal liver (58). For this reason, in this study we have used CD90(Thy‐1) mAb, which is a widely accepted marker in studies evaluating rat hematopoiesis (58–62). We have confirmed that immature donor‐origin cells (CD90+), which represent 21% to 45% of all nucleated BM cells (59), play a major role in efficacy of engraftment and chimerism development as early as day 7 posttransplant.…”
Section: Discussionmentioning
confidence: 99%
“…Thy-1 (CD90) is a GPI-anchored membrane glycoprotein of the Ig superfamily which is involved in signal transduction (1618), and it is expressed by a wide spectrum of hematopoietic stem and progenitor cells (1619), as well as non-hematopoietic cells, including neurons (16), edothelium at inflammatory sites (20), and hepatic OC (21, 22). High purity OC enrichment is achieved through IMS using the OC surface marker Thy-1.…”
Section: Methodsmentioning
confidence: 99%